The Application of The Right Brain Methods : The Association and Correlation Method In Optimizing Vocabulary Mastery at The Seventh Grade Students of SMPN 1 Rancah-Ciamis: The Application of The Right Brain Methods : The Association and Correlation Method In Optimizing Vocabulary Mastery at The Seventh Grade Students of SMPN 1 Rancah-Ciamis - Meiliana Nurfitriani (NATURALISTIC : Jurnal Kajian Penelitian Pendidikan dan Pembelajaran, 2016)
This study investigated the application of the right brain methods, namely the association and correlation method in optimizing the students’ vocabulary mastery at the seventh grade of SMPN 1 Rancah Ciamis. It uses the qualitative approach by using Classroom Action Research (CAR) to determine how the right brain methods help students in optimizing vocabulary mastery, and to analyze how the students’ progress related to the right brain methods in optimizing vocabulary mastery in the seventh grade students of SMPN 1 Rancah. This study is conducted in three cycles, each of which consisted of planning, acting, observing, and reflecting. The data of the study are taken from the questionnaire, observation, interview and the students’ vocabulary test in form of multiple choice and students’ presentation. Data analysis techniques used are descriptive analysis both qualitatively and quantitatively. The results show that the implementation of the right brain methods, namely the association and correlation method affected possitively on the improvement of students’ vocabulary mastery. It is based on the enthusisatic and the active participation of the students in the process of teaching and learning, and also the results of students’ vocabulary test from pre-cycle to cycle III.